PENGARUH BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2019-2023 - Yuli Rahmawati; Rissa Andharini; Resa Anandita; Berliana Putri; Rahma Rina Wijayanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research discusses the influence of capital expenditure on economic growth in East Java Province. Economic growth is an increase in economic activity in a country or region, which is reflected in an increase in per capita output and overall community income. Capital expenditures are used for expenditures in the purchase or construction of tangible fixed assets that have a useful value of more than 12 months. This research uses quantitative methods with an associative approach and secondary data from the East Java Province APBD Financial Report. The research hypothesis is that capital expenditure has a positive and significant influence on economic growth in East Java Province. Data analysis methods include partial t-test, F test, coefficient of determination test, and classical assumption test. Skewness and kurtosis can indicate whether the data is normally distributed or not. The multicollinearity test is used to see the relationship between variables in the regression model. The autocorrelation test is used to determine the presence of autocorrelation in the regression model. The heteroscedasticity test is used to indicate the presence of interference in the regression model. The research results show that capital expenditure does not have a significant effect on economic growth in East Java Province.